Combined GPS+BDS+Galileo+QZSS for long baseline RTK positioning - Odolinski, R.; Teunissen, Peter; Odijk, Dennis (Institute of Navigation, 2014)
In this contribution we will focus on long single-baseline real-time kinematic (RTK) positioning when combining the American GPS, Chinese BDS, European Galileo and Japanese QZSS. The main objective is to demonstrate the potential benefits for RTK when combining the next generation GNSSs, as compared to using the systems separately. With long baseline we refer to the necessity to model the slant ionospheric delays by the ionosphere- float strategy. The (wet) Zenith Tropospheric Delay (ZTD) will be estimated as well. The ionosphere-float model implies that the slant ionospheric delays are assumed completely unknown. We will focus on overlapping frequencies between the systems. The advantage with overlapping frequencies is that the redundancy of the model can be maximized if the inter-system biases (ISBs) can be calibrated. This also allows for a common pivot satellite between the systems when parameterizing the double-differenced integer ambiguities. It will be shown that with the ionosphere-float model at least two overlapping frequencies between the systems are required to benefit from calibration of ISBs. The GNSS real data is collected in Perth Australia, a country where the multi-system satellite visibility is almost at a global maximum. The single-baseline RTK performance is evaluated by a formal and empirical analysis, consisting of ambiguity dilution of precision (ADOP), bootstrapped success rates and positioning precisions. It will be shown that the combination of the four systems provides for shorter ambiguity/positioning convergence times, improved integer ambiguity resolution and positioning performance over the single-, dual- and triple-systems.